DAYA ANTIBAKTERI EKSTRAK ETANOL BUAH PACE (Morinda citrifolia, L) TERHADAP BAKTERI Shigella dysentriae SECARA IN VITRO SERTA PROFIL KROMATOGRAFI LAPIS TIPIS - Nurcahyani, Diah (Widya Warta, 2016)
Pace fruit (Morinda citrifolia, L) is known by people as an ingredient of beverage. In addition, the people take it as medicine for dysentery. It was carried out a study with the intention of observing the antibacterial activity of extract of pace fruit, on bacteria Shigella dysentriae. The dried fruit was pounded to powder then a filtering was made employing Soxhlet, with ethanol as the extractor. The extract had been obtained was then evaporated to achieve viscosity and it was made a serial of dilution in various concentration, namely, 2,5%, 5%, 10%, and 20% b/v by propilen glikol solvent and an examination was performed for the activity of antibacterial involved. To negative control it was used propilen glikol and while positive control it was used kanamizi. Bacteria used was Shigella dysentriae. The examination adapted the method of Nutrient gel solid diphusy to see Minimal Obstacle Rate (Kadar Hambat Minimal). The outcome of antibacterial test showed that the extract of pace demonstrated antibacterial activity on Shigella dysentriae, at a minimal obstacle rate 20% b/v. To see the chemical content of pace fruit, it was performed thin chromatography on the extract of pace fruit to observe the profile of spots involved. The outcome of examination for the content of compound under ultra violet ray 254 nm and 366 nm, showed that the extract of pace was possibly containing fenol compound.